Film-viewing in Turkish and Moroccan diasporic families: a gender and place perspective. Issue 4 (2nd April 2016) - Smets, Kevin; Van Bauwel, Sofie; Meers, Philippe; Vande Winkel, Roel
Abstract : This article explores the relation between gender identities and spatial aspects of audience reception by means of a case study on film-viewing in the Turkish and Moroccan diasporic communities in the Belgian city of Antwerp. Drawing on feminist and gender approaches to audience reception on the one hand, and research into the spatial dynamics underlying audience reception on the other, we look at film-viewing as a socially and spatially meaningful practice that is relevant for the understanding of gender identities in diasporic families. This article is based on the results of a four-year project on diasporic film cultures in Antwerp that investigated how film-viewing practices relate to social and cultural dynamics within the Turkish and Moroccan communities. The data that are discussed include participant observations, in-depth interviews and group interviews with a varied sample of people with Turkish and Moroccan backgrounds. The results show that although film-viewing, especially in the public space of the film theatre, can be mobilized by women as an emancipating social practice, gendered power structures often prevail. Also in the domestic contexts, a more traditional gender division is articulated by the respondent concerning family viewing. We conclude that the space of the film theatre and film-going serve the continuity and stability of gendered family relations, rather than subverting them.